TECHNETIUM-99M MIBI GATED MYOCARDIAL PERFUSION SINGLE PHOTON EMISSION COMPUTED TOMOGRAPHY IMAGING – VALIDATION OF STRESS ONLY PROTOCOL - Zaigham Salim Dar (Army Medical College Rawalpindi, 2021)
Objective: To validate ‘stress only’ protocol against ‘rest stress protocol in normal and essentially normal cases undergoing Tc99m MIBI gated myocardial perfusion Single Photon Emission Computed Tomography imaging.